Survey of Effective Factors in the Event of Neuropathy in Type 2 Diabetic Patients - Sadegh Kargarian Marvasti; Shahnaz Rimaz; Jamileh Abolghasemi; Iraj Heydari (Journal of Kerman University of Medical Sciences, 2017)
Introduction: Diabetic neuropathy is a common and sever complication of diabetes that its progression can lead to disability and even amputation in diabetic patients. The aim of this study was to determine the effective factors in the event of neuropathy and to assess the cumulative incidence of neuropathy in patients with type 2 diabetes. Methods: In this cohort study, all patients with type 2 diabetes who were registered at Fereydunshahr Diabetes Clinic, Isfahan, Iran, were selected by census method. They were followed up for diagnosis of neuropathy since 2006 until March 2016. To investigate the quantitative and qualitative effective factors in the event of neuropathy, one-sample t-test and chi-square test, respectively, were used. And for modeling of effective factors in the event of neuropathy, logistic regression was used. All statistics were analyzed by R software (version 3.2.3) and P values less than 0.05 were considered significant. Results: At the end of 10-year follow-up, cumulative incidence and prevalence of neuropathy were estimated 31% and 41.6%, respectively. After removal of confounders in the final model, variables such as age, ethnicity, family history of diabetes, duration of diabetes, FBS and HDL levels were identified as effective factors in the event of neuropathy (p <0.05). Conclusion: Low levels of HDL and poor control of FBS level are modifiable risk factors for diabetic neuropathy. But non-modifiable risk factors include Persian ethnicity, family history of diabetes, age and increase of diabetes duration. For this reason, in order to increase the HDL level and to decrease FBS level, education is recommended particularly in elderly patients with a family history of diabetes.